What do you know about animal adaptations? - Slade, Suzanne (New York : PowerKids Press, 2008)
Explores twenty questions about animal adaptation, covering such topics as hibernation, camouflage, and habitats.
Includes index.
3.0
K-3
Keywords: Animals -- Adaptation -- Miscellanea -- Juvenile literature; Animals -- Adaptation; Animal behavior; Animals -- Habitat; Animals -- Adaptation; Questions and answers